Evaluation of the medical care quality indicators for the pharmacotherapy of patients with ischemic stroke: a hospital-based study - Levytska, Oksana; Hromovyk, Bohdan; Ryvak, Tetiana; Kostyana, Kateryna (Archives of Pharmacy, 2020)
Ischemic stroke belongs to the leading causes of death and disability in the world and Ukraine. The surviving rates depend on the quality of the provided medical care. The research aimed to analyze the quality of medical care related to pharmacotherapy of ischemic stroke. The clinical indicators for quality are the quantitative or qualitative indicants that have evidence or consensus of direct influence on it. Six of them relate to acute ischemic stroke pharmacotherapy (namely, thrombolytic, antiplatelet, anticoagulant, and lipid-lowering agents use at different stages of hospital stay) and were investigated in this retrospective analysis of 151 patients’ medical records of one of the specialized hospital departments in Lviv city. The clinical indicators for quality of medical care showed that pharmacological treatment using antithrombotics (antiplatelets and anticoagulants) at the admission to the hospital corresponded to standards and quality was defined as high with rates of 65.6% and 85.4%. At discharge, the indicator analysis of pharmacotherapy revealed existing problems for antithrombotic (2 indicators) and lipid-lowering (1 indicator) pharmacotherapy with rates of 33.3% and 47.7%. The outcomes concluded the existence of problems related to pharmacotherapy. The complex of three algorithms was introduced to improve the quality of medical care.